2022
DOI: 10.1136/bmjopen-2021-059821
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural intentions in response to a potential menthol cigarette sales ban: a survey examining smokers in Washington, DC public housing

Abstract: ObjectivesLocal, national and international policies are being proposed to ban the sale of menthol-flavoured tobacco products. With more bans being implemented, it is increasingly important to understand reactions to these bans among smokers of low socioeconomic status. This study examined public housing residents’ behavioural intentions if menthol-flavoured cigarettes were no longer sold.Setting15 District of Columbia Housing Authority properties between March 2019 and March 2021.Participants221 District of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…One study asked respondents about their interest to several alternative products first and only the 2.6% who claimed that they would not initiate or keep any products were taken as ‘would try to quit’ 22. On the other hand, another study that found 48% would try to quit asked about intention to quit first, then asked about alternative product use only among respondents who said they would not try to quit 23…”
Section: Discussionmentioning
confidence: 99%
“…One study asked respondents about their interest to several alternative products first and only the 2.6% who claimed that they would not initiate or keep any products were taken as ‘would try to quit’ 22. On the other hand, another study that found 48% would try to quit asked about intention to quit first, then asked about alternative product use only among respondents who said they would not try to quit 23…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a previous study suggesting that approximately 75% of individuals of lower SES who live in public housing would quit smoking under a menthol cigarette ban. 37 Additionally, more affluent groups purchased more alternative tobacco products under unrestricted flavor policies, suggesting they may have more experience or are more willing to try new products than individuals of lower SES. As with NRT, this finding might reflect greater access or exposure to alternative tobacco products.…”
Section: S108mentioning
confidence: 99%
“…Mentholated cigarettes increase smoking initiation, especially in youth populations, encourage greater nicotine dependence and results in lower cessation rates compared to non-mentholated cigarettes 146 . These relationships have led to bans on the sale of menthol cigarettes in Canada, England and the European Union 38,79 and a proposed ban in the United States of America 34 .…”
Section: Composition Intake and Kineticsmentioning
confidence: 99%